Childhood Clear Cell Sarcoma of Kidney: Incidence and Survival - Gao, Hui; Cheng, Qi-Yuan; Zhao, Qian; Tao, Long-Xiang; Zhang, Cheng (Frontiers in Pediatrics, 2021)
This study is to describe current incidence of childhood clear cell sarcoma of kidney (CCSK) and to investigate the present survival of this cancer. Surveillance, Epidemiology, and End Result (SEER) data was used to identify children with CCSK and Wilms tumor (WT) aged 0-19 years in the US. Age-adjusted incidences were estimated over the decades. Age- and sex-specific epidemiology was also presented. Propensity score matching was used to balance features of CCSK and WT cases. Log rank test was used to compare survivals and Cox regression was used to evaluate independent effects of factors. The present age-adjusted incidence of childhood CCSK was 0.205 per million, which remained stable for years and ranked third in all pediatric renal tumors. The incidence rate ratios for boy and age under 4 were 3 and 21, respectively. The current 5-year overall survival (OS) rate for CCSK was 87%, which is not evidently inferior to that for WT (90%); however the outcome of CCSK was significantly poorer if both groups were well balanced (OS rate was 86% versus 95%). Early year of diagnosis and distant metastasis were independent survival factors. In conclusion, occurrence of CCSK remains stable over the years, with an age-adjusted incidence of 0.205 per million. Boy and age under 4 are risk factors for tumor development. CCSK currently has a favorable outcome but its nature may be more aggressive than common kidney tumor, which in turn proves efficacy of modern treatment.